2020
DOI: 10.1101/2020.05.13.093781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Vitro Inhibition of SARS-CoV-2 Infection by Bovine Lactoferrin

Abstract: Since its emergence in late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been posing a serious threat to public health worldwide as the causative agent of coronavirus disease 2019 . Now distributed in a pandemic pattern, this disease still lacks an effective drug treatment with low toxicity, leading pharmaceutical companies and research labs to work against time to find a candidate molecule to efficiently treat the affected patients. Due to the well-known broad-spectrum antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
2
8
0
1
Order By: Relevance
“…New findings and highlights of our study include: 1) BLF and HLF have broad-spectrum antiviral activity against infectious SARS-CoV-2, HCoV-OC43, HCoV-NL63, and HCoV-229E viruses in cell culture. It is noted that in parallel to our study, two preprints in biorxiv independently confirmed the antiviral activity of LF against SARS-CoV-2 [50,51].…”
Section: Discussionsupporting
confidence: 86%
“…New findings and highlights of our study include: 1) BLF and HLF have broad-spectrum antiviral activity against infectious SARS-CoV-2, HCoV-OC43, HCoV-NL63, and HCoV-229E viruses in cell culture. It is noted that in parallel to our study, two preprints in biorxiv independently confirmed the antiviral activity of LF against SARS-CoV-2 [50,51].…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were shown for Zika and Chikungunya virus [166]. More recently, lactoferrin has been shown to be able to inhibit about 85% of SARS-CoV-2 infection in Vero cells [167].…”
Section: Antiviral and Immunomodulatory Effects Ofsupporting
confidence: 82%
“…Indeed, it has been reported that lactoferrin takes part in the host immune response against severe acute respiratory syndrome coronavirus (SARS-CoV) invasion by enhancing NK cell activity, stimulating neutrophil aggregation and adhesion and preventing the interaction between the viral particle and its cell receptors, represented by heparan sulfate proteoglycans (HSPGs) [54]. Starting from this evidence, similar mechanisms have been proposed for SARS-CoV-2 (COVID-19) infection, for which lactoferrin has additionally shown the capability of inhibiting in vitro viral replication [55].…”
Section: Lactoferrin and Infectionsmentioning
confidence: 86%